The effect of aerobic exercise and consumption of vitamin B6 and omega-3 on the expression of genes related to autophagy caused by endometriosis in female rats - Zahra Rezaie; Parvin Farzanegi; Hajar Abbaszadeh (Shahid Beheshti University, 2023)
Background and Purpose: Endometriosis is an estrogen-dependent inflammatory disease that affects 5-10% of women of reproductive age. Different cellular pathways are involved in the pathogenesis of endometriosis. One of these pathways is autophagy. Autophagy is a genetically and evolutionarily conserved programmed process that degrades long-lived cellular proteins and organelles. The aim of this study was to investigate the effect of aerobic exercise and consumption of vitamin B6 and omega-3 on the expression of genes related to autophagy caused by endometriosis in female rats.Materials and Methods: In this experimental study, 40 adult male Wistar rats were about eight weeks old. After transferring the rats to the laboratory environment and after two weeks of familiarization with the new environment and creating the endometriosis model, randomly and with an equal number of five rat in each group, they were divided into the control-healthy, endometriosis, sham, endometriosis+exercise, endometriosis+B6, endometriosis+omega-3, endometriosis+exercise groups after creating an endometriosis model+ B6, endometriosis+exercise+omega-3 were categorized. The duration of training in the water was 30 minutes daily until the end of the training period. Two weeks after the creation of the model, omega-3 supplement at a dose of 2 ml/kg to the endometriosis+omega-3 and endometriosis+exercise+omega-3 groups and vitamin B6 supplement at the rate of 60 kg/mg body weight of the rats to the groups endometriosis+B6 and endometriosis+exercise+B6 were taken daily in the form of gavage. One-way analysis of variance was used to analyze the data.Results: The results showed that the expression levels of LC3-1 and LC3-II genes in the endometriosis group were significantly higher than the healthy control group (P<0.0001) and the expression levels of LC3-1 and LC3-II genes in the group endometriosis+exercise, endometriosis+omega-3, endometriosis+B6, endometriosis+exercise+B6 and endometriosis+exercise+omega-3 were significantly lower than the endometriosis group (P<0.0001). Their values in endometriosis+exercise+B6 and endometriosis+exercise+omega-3 groups were significantly lower than other groups (P<0.0001). Also, the results showed that the expression levels of FOXO3 and LC3-II/I genes in the endometriosis group were significantly lower than in the healthy control group (p<0.0001). The expression levels of FOXO3 and LC3-II/I genes in endometriosis+exercise, endometriosis+omega-3, endometriosis+B6, endometriosis+exercise+B6 and endometriosis+exercise+omega-3 groups were significantly higher than the endometriosis group (P<0.05). Their values in endometriosis+exercise+B6 and endometriosis+exercise+omega-3 groups were significantly higher than other groups (P<0.0001).Conclusion: In general, the results of the present research indicate that the increased expression of autophagy genes that occurs in endometriosis can be inhibited by regular aerobic exercise such as swimming and omega-3 and B6 supplements. Probably, the pathological disorder caused in autophagy by exercising and supplementing omega-3 and B6 through the regulatory reduction of the expression of lc3-I, lc3-II genes and the increase of the expression of FOXO3 genes and the ratio of lc3-II / lc3-I helps in improving endometriosis.